The impact of influencer credibility on purchase intention in the endorsement of sustainable products - Kiss, Réka (2021)
Influencer marketing has been on the rise in recent years, and most brands have collaborated with social media influencers. Hence, scholars have studied the topic focusing on the effects of influencer credibility on brand awareness, attitude towards the brand and the advertisement, and purchase intention. Moreover, sustainability has become essential for brands and consumers. However, influencer credibility regarding sustainable products is understudied. Thus, this study aimed to fill the research gap regarding the endorsement of sustainable products through social media influencers. The current research focused on Instagram, as it is currently the most popular platform for influencer marketing. The study utilized the most commonly used constructs for influencer credibility and studied how the influencer's expertise, trustworthiness, attractiveness, and similarity affect their followers' purchase intentions. Additionally, the followers' sustainability behavior was examined as it affects their purchase intention regardless of the influencer's endorsement. The study was conducted through quantitative research. Followers of two Finnish Instagram influencers answered a survey (n=165) distributed through Instagram direct messages and Jyväsklyä University's email list. The collected data were analyzed in IBM SPSS Statistics 26 and Smart-PLS 3.0. The analysis showed that the influencer's field of expertise did not affect their credibility regarding the endorsement of sustainable products. Moreover, the results indicate that similarity and trustworthiness highly affect followers' purchase intentions, while expertise has no effect, and attractiveness has a negative effect. In terms of sustainability, the study found that the followers' existing sustainability behavior moderates the effects of influencer credibility on purchase intention. Overall, the study contributed to the existing literature of influencer credibility, however, with a focus on sustainability. Additionally, the study not only extended the literature on the topic but discussed several managerial applications that can help marketers to make better decisions regarding their social media influencer collaborations.